PENGARUH JINGLE IKLAN VERSI â€œBABY SHARKâ€ TERHADAP BRAND AWARENESS SHOPEE INDONESIA SURVEI PADA PEMIRSA JINGLE IKLAN SHOPEE INDONESIA DI KOTA BANDUNG - Herawaty, Tetty; Rahmah, Saffanati; Syafa'atul Barkah, Cecep (IMAGE : Jurnal Riset Manajemen, 2021)
The phenomenon of e-commerce which is increasingly prevalent in Indonesia will certainly result in consumers being more selective in choosing the desired brand. So that the company tries to build a brand in the minds of consumers, by using ad jingles. This study aims to determine the effect of advertising jingles and brand awareness on Shopee Indonesia. The objects examined in this study are jingles and brand awareness. The research method is descriptive analysis verification by the survey. The survey was conducted on visitors who view the Shopee Indonesia advertising jingle in Bandung, through a questionnaire, totaling one hundred and sixteen respondents. Samples were obtained based on iteration calculations and carried out by purposive sampling. This type of research is used quantitatively by testing the hypothesis. The method used is simple regression analysis, correlation analysis, and the coefficient of determination in finding the influence of advertising jingles (x) with brand awareness (y). The results of this study indicate that advertising jingles have a positive effect on brand awareness. The resulting Pearson correlation coefficient is positive. This research shows that there is an influence between advertising jingles on brand awareness. Based on hypothesis testing, this study states that advertising jingles have a positive effect on brand awareness.Â Â Â